Iconic transition: alternatives and choices in education - Aleksandr A. Polonnikov (Высшее образование в России)
The main theme of this paper is the content of professional mediation in an educational context a culturally, scientifically, and educationally diverse settings. The actor’s choice of an educational strategy is presented as a complex act of self-identification requiring appropriate support. The traditional function of educational mediation, understood as the transfer of specific orientations to the individual, is juxtaposed with an overall pattern of mediation that treats the orientation context as a matter for objectivation and selection. “Iconic transition” is considered as a model for mediation, its effectiveness is linked to the specifics of text organization. “Iconic transition” is de-objectivised and presented as an intermediate semiotic construct created within education serving to renew its functioning mode.